Introducing the "Getting Found" Web Analytics Cookbook for Monitoring Search Engine Optimization of Digital Repositories - Arlitsch, Kenning; OBrien, Patrick (Qualitative and Quantitative Methods in Libraries, 2017)
A new toolkit that helps libraries establish baseline measurements and continuous monitoring of the search engine optimization performance of their digital repositories is one of the products of research funded by the Institute of Museum and Library Services. The “Getting Found” Cookbook includes everything necessary for implementing a Google Analytics dashboard that continuously monitors SEO performance metrics relevant to digital repositories. While the Cookbook has been created for use with Google Analytics, the principles and practices described can be applied to any page tagging analytics software.